A Comprehensive Comparison and Analysis of Several Intensity Modulations Based on the Underwater Photon-Counting Communication System - Han, Xiaotian; Li, Peng; Chang, Chang; Gao, Duorui; Zhang, Dongquan; Liao, Peixuan; Wang, Wei; Xie, Xiaoping (Frontiers in Physics, 2022)
Underwater wireless optical communication is facing absorption, scattering problems, which, in principle, can be greatly resolved by underwater photon-counting communication (UPCC) technology that exhibits high-sensitivity communication characteristics in long-range underwater wireless optical communication. Recent studies on UPCC are mainly focused on a single intensity modulation such as on–off keying (OOK) and pulse position modulation (PPM) technologies, and the comprehensive analysis of communication performance combing OOK modulation and digital pulse modulations remains a lack. To this, by using a UPCC system based on a single-photon avalanche diode, we reveal the communication performances of OOK, PPM, differential pulse interval modulation (DPIM), differential pulse position modulation (DPPM), and dual-header pulse interval modulation, and find that (1) the PPM has the longest transmission distance at the same bit error ratio when M > 2, but the lowest communication rate under identical modulation bandwidth and average transmit power; and (2) the DPPM and DPIM perform the optimum communication performance at the fixed communication rate when M = 8. We thus conclude that the DPPM and DPIM have advantages of low modulation bandwidth and long time slot time compared with PPM, indicating the significance of reducing the difficulty of signal synchronization and the complexity of the underwater photon-counting system accordingly.